2009
DOI: 10.1016/j.ajog.2008.07.069
|View full text |Cite
|
Sign up to set email alerts
|

The effects of male circumcision on female partners' genital tract symptoms and vaginal infections in a randomized trial in Rakai, Uganda

Abstract: Objective-To assess effects of male circumcision on female genital symptoms, and vaginal infections.Methods-HIV-negative men enrolled in a trial were randomized to immediate or delayed circumcision (control arm). Genital symptoms, BV and trichomonas were assessed in HIV-negative wives of married participants. Adjusted prevalence risk ratios (adjPRR) and 95% confidence intervals (95%CI) were assessed by multivariable log-binomial regression, intent-to-treat analyses.Results-783 wives of control and 825 wives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
4
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(203 citation statements)
references
References 17 publications
5
188
4
6
Order By: Relevance
“…81 A small prospective cohort study with good evidence also found that male circumcision, among other factors, was protective against BV in female partners. 82 A cross-sectional study with fair evidence found no effect but may have lacked the power to detect an effect.…”
Section: Bvmentioning
confidence: 99%
“…81 A small prospective cohort study with good evidence also found that male circumcision, among other factors, was protective against BV in female partners. 82 A cross-sectional study with fair evidence found no effect but may have lacked the power to detect an effect.…”
Section: Bvmentioning
confidence: 99%
“…269 Male circumcision has been prospectively associated with a 966 significant reduction in BV-associated genera, 263,264 and a striking 40-60% reduction in BV 967 incidence in female partners over 12 months. 270 Although there are few studies, BV-968 associated biofilm has been detected in male urine and semen, and more commonly found in 969 male partners of women with BV than healthy controls. 225,271,272 Collectively, these data The concept of a "symptomatic male disease counterpart" has not received much attention.…”
mentioning
confidence: 99%
“…There is also evidence for reduced partner genital infections cancer, for example, reduced partner bacterial vaginosis [20,21] HPV and reduced cervical cancer risk [6,[20][21][22][23][24]. MC however does not offer any protection against Neisseria gonorrhoeae, Chlamydia Trachomatis or Trichomomonas vaginalis [25].…”
Section: The Known Risks and Benefits Of MC Is A Public Health Mc Prmentioning
confidence: 99%